PERAN PROFITABILITAS DALAM MEMODERASI PENGARUH FIRM SIZE DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - Azizah, Mega Nur; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2024)
Indonesia has entered the era of the industrial revolution 4.0 which is clearly visible with an increase in connectivity, interactivity, and boundaries between humans, machines, and resources on information technology and other communications. Judging from the current business world on the aspect of competition, the Indonesian economy is increasingly experiencing major developments. The transportation and logistics sector has an important role in people's lives driven by the increasing needs of the community for mobility and transportation of goods to all regions. Despite the ongoing economic crisis, transportation services will continue to operate smoothly because people will continue to use them to send goods from producers to consumers, regardless of the conditions in which they work. The purpose of this study was to analyze and test the role of Profitability in Moderating the effect of Firm size and Leverage on Firm value. The population in this study were transportation and logistics companies with 37 companies listed consecutively on the Indonesia Stock Exchange during 2019-2022. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing using Structural Equation Analysis - Partial Least Square (PLS-SEM). The results of research hypothesis testing using the Smart PLS 3.0 application, show that Firm size has a significant negative effect on firm value, Leverage has a significant positive effect on firm value, Profitability does not significantly moderate the effect of Firm size on firm value, Profitability does not significantly moderate the effect of Leverage on firm value.